A Cephalometric soft-tissue Analysis of Filipino Adults with Esthetic Profiles - De Veyra, Rosabelle Felicia F.
The purpose of this investigation was to determine the facial profile of choice for Filipinos, and to formulate soft-tissue guidelines for use with such patients seeking orthodontic treatment or orthognathic surgery for dentofacial disharmonies.To be able to identify normative values for acceptable Filipino soft-tissue profiles, the cephalometric profile line drawing of 30 Filipinos aged 18-25 years were assessed by a group of 36 judges consisting of medical and dental practitioners, artists, beauty experts, and lay persons. Nine profiles were rated as esthetic by the judges, and were evaluated according to Holdaway's Soft-tissue Analysis.The mean, range, and standard deviation values for each of the 11 parameters measured were obtained and compared with white and Chinese norms. The results of this investigation indicate that the acceptable Filipino facial form in comparison with Caucasian and Chinese profiles in generally more convex owning to a weak chin, and has more prominent upper and lower lips.